2020
DOI: 10.1108/jmd-05-2019-0194
|View full text |Cite
|
Sign up to set email alerts
|

君子 Junzi leadership in Singapore: governance and human capital development

Abstract: PurposeThis paper provides insights as to how a Confucian-inspired Junzi style of leadership translates into initiatives toward human capital development in Singapore. After reviewing tripartite governance in Singapore, we discuss the character of Confucian leadership: how does this value system inform the moral economy of the Singaporean corporatist model and inherently come to impact upon the conception and significance of human capital.Design/methodology/approachThe case approach was employed using multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In addition, school principals explore social justice in driving school improvement (Caliskan, 2020). Le Queux and Kuah (2020) said that school leaders in Singapore use the Junzi Leadership to serve the school stakeholders for school performance. They said Confucian Junzi (gentlemen) sought Grace and dignity by fulfilling traditional obligations: "Confucian rationalism meant rational adjustment to the world" (p.393).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, school principals explore social justice in driving school improvement (Caliskan, 2020). Le Queux and Kuah (2020) said that school leaders in Singapore use the Junzi Leadership to serve the school stakeholders for school performance. They said Confucian Junzi (gentlemen) sought Grace and dignity by fulfilling traditional obligations: "Confucian rationalism meant rational adjustment to the world" (p.393).…”
Section: Discussionmentioning
confidence: 99%
“…They said Confucian Junzi (gentlemen) sought Grace and dignity by fulfilling traditional obligations: "Confucian rationalism meant rational adjustment to the world" (p.393). Therefore, they emphasize that leaders need to use the Confucian moral core, including Ren/benevolence, Yi/rightness, and Li/norms, to improve the school (Le Queux & Kuah, 2020). Therefore, it was found that Chinese school principals emphasize the importance of the hightesting score performance and promote the educational core values for school sustainability and lifelong learning.…”
Section: Discussionmentioning
confidence: 99%
“…Multiculturalism existed in each context, yet has taken different trajectories: cohabitation under segregation for the former, unity with some degree of subordination to the "core," for the latter. Indeed, while the Malaysian NEP was ostentatiously designed and branded to advance the Bumiputeras social hegemony, from the late 1970s onward, New Confucianism served as a catalyst for identity building, marked by a "sino-centric nation building narrative" in Singapore (Pezzutto, 2019, p. 232, in Le Queux andKuah, 2020). This state-sponsored narrative provided background legitimacy to indirect forms of elitism and meritocracy in favor of the Singaporean power base (Teo, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This view is echoed by an official statement that Trade and Industry Minister made in 2019: "As our multicultural social norms can be rather unfamiliar to foreign employees, it is important that businesses also play a part in integrating them into our companies and into our society" (The Straits Times, 2019b). Hence, recent initiatives to address the challenge of "partially incorporating" the migrant workforce Le Queux, 2013, 2014) and to upskill the Singaporean "Core" [1], with the view that enhanced human capital will lead to productivity gains, therefore alleviated the need for migrant labor (Kuah et al, 2017;Le Queux and Kuah, 2020).…”
Section: Indicatorsmentioning
confidence: 99%
“…Other authors developed the student's motivation and skills to fulfill the school goals (Li, Liu, Chen, Yeh, & Yeh, 2017). Once the students have grit, they usually can face challenges with values of education, such as discipline, harmony, morality, peace, and self-cultivation (Queux & Kuah, 2020). The transformational leaders need to invite students, teachers, and parents for school improvement in using the educational values as transformative school culture.…”
Section: Literature Reviewmentioning
confidence: 99%